Indoor Channel Modelling for SISO and Massive SIMO in the 60 GHz mm-Wave Band - Yuksekkaya, Baris (Elektronika ir Elektrotechnika, 2017)
In this paper, an indoor two dimensional channel modeling scheme is proposed for fifth generation (5G) 60 GHz millimeter-wave (mm-wave) communication systems. mm-wave systems are one of the most important candidate technologies to be used in 5G communications because of their advantages such as wide bandwidth, high power communication allowance and small sized, massive numbered antenna arrays. Therefore, modeling of the characteristics of the millimeter-wave channel is substantial.Characterization and modeling studies of mm-wave channels were performed using ray tracing method for both single and massive numbered antennas. The results in terms of multipath delay spread and multipath power content are investigated and a useful simulation is created that will be used to test future hardware implementations. DOI: http://dx.doi.org/10.5755/j01.eie.23.4.18720